Mobile robots [ - Burkhart, Pamala (New York : The English Press, 2014)
This book has been written with the purpose of covering all aspects about mobile robots
1. Mobile robots -- 2. Aerobot -- 3. Android (robot) -- 4. Powered exoskeleton -- 5. Automated guided vehicle -- 6. Autonomous underwater vehicle -- 7. Gynoid -- 8. Humanoid robot -- 9. Remotely operated underwater vehicle
Keywords: Mobile robots